2011
DOI: 10.1021/jm101327d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cationic Antimicrobial β2,2-Amino Acid Derivatives with Potential for Oral Administration

Abstract: We have prepared a series of highly potent achiral cationic β(2,2)-amino acid derivatives that fulfill the Lipinski's rule of five and that contain the basic structural requirements of short cationic antimicrobial peptides. Highest antimicrobial potency was observed for one of the smallest β(2,2)-amino acid derivatives (M(w) 423.6) exhibiting a MIC of 3.8 μM against methicillin-resistant Staphylococcus aureus (MRSA), methicillin-resistant Staphylococcus epidermidis (MRSE), and Staphylococcus aureus, and 7.7 μM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 50 publications
2
47
0
Order By: Relevance
“…The most potent compounds were those in which the lipophilic moiety was based on tert-butyl-substituted benzenes. [62] As et of novel cationic amphiphilic small-molecule biocides was also reported by our group (Table 9, Structure 29). Three important features of these compounds include:1)variable hydrophobic character,n ot only from pendentl ipophilic alkyl chainsb ut also from the lipophilic spacer chains in their design; 2) inclusion of non-peptidica mide bonds in the lipophilic alkyl chains;a nd 3) permanent positivec harges from quaternary ammonium groups instead of soft charges provided by naturala mino acids.…”
Section: Other Interesting Designssupporting
confidence: 66%
“…The most potent compounds were those in which the lipophilic moiety was based on tert-butyl-substituted benzenes. [62] As et of novel cationic amphiphilic small-molecule biocides was also reported by our group (Table 9, Structure 29). Three important features of these compounds include:1)variable hydrophobic character,n ot only from pendentl ipophilic alkyl chainsb ut also from the lipophilic spacer chains in their design; 2) inclusion of non-peptidica mide bonds in the lipophilic alkyl chains;a nd 3) permanent positivec harges from quaternary ammonium groups instead of soft charges provided by naturala mino acids.…”
Section: Other Interesting Designssupporting
confidence: 66%
“…molecules for therapeutic applications (41)(42)(43)(44). Extending our previous findings with the N-terminally tagged dipeptide spermidine template, in the present work we designed two series of peptidomimetics (series 1 and 2) with linear or branched arrangements of Trp residues on the spermine backbone to explore the effects on antibacterial activity and selectivity and the mode of action.…”
Section: Discussionmentioning
confidence: 88%
“…Thus, SMAMPs are versatile for optimization of both antimicrobial potency, pharmacokinetic properties, and reduction of toxicity. We have reported a series of α,α‐disubstituted β 2,2 ‐amino amides, as represented by the SMAMP 7b in Figure , that display high antimicrobial activity against gram‐positive bacteria . In the present study, we have incorporated two halogenated α,α‐disubstituted β 2,2 ‐amino acid residues into an amphipathic 13‐membered cyclic tetrapeptide scaffold and explored their antimicrobial activity (Figure ).…”
Section: Introductionmentioning
confidence: 96%
“…Two series of peptides were synthesized each containing one of two selected α,α‐disubstituted β 2,2 ‐amino acids (Figure ). The substituents on the α‐carbon of the achiral β 2,2 ‐amino acids were either 4‐trifluoromethylbenzyl or 3,5‐di‐trifluoromethylbenzyl, in which previous studies has shown to improve antimicrobial potency of small SMAMPs and minimize hepatic Phase I oxidation by including lipophilic side‐chains with a trifluoromethyl substituent . The effects of charge and lipophilicity were further varied by substituting one of the three α‐amino acids with l ‐Lys, Gly, l ‐Ala, or l ‐Phe residues, i.e., residue Xaa in the general cyclic tetrapeptide sequence c(Lys‐β 2,2 ‐Xaa‐Lys) (Figure ).…”
Section: Introductionmentioning
confidence: 99%